La selección por competencias y su influencia en el desempeño de los trabajadores de Rivolta Street Pasta - Tang Choy, Marisol (2023)
The purpose of this research is to determine the influence of the competency-based selection process on the performance of Rivolta Street Pasta employees. Therefore, it is intended to contribute to management with information that is lacking in this type of small companies, as is the case of Rivolta Street Pasta. The variables that are developed are: selection by competencies and work performance, which are used for the workers of Rivolta Street Pasta. The type of research applied is qualitative, since the relationship between the two variables will be investigated. For this reason, surveys were conducted with customers and owners, and in-depth interviews were conducted with experts on the subject. The results obtained showed that the workers lacked the competencies required by the company and this could be perceived through the surveys to customers and owners, reaching the conclusion that the absence of competencies is due to the fact that a correct selection by competencies is not carried out in the restaurant.